The Use of Information Technologies in Primary School Students Teaching: the Experience of Japan. - Федірчик, Тетяна; Bakhmat, Nataliia (Małgorzata Stawiak-Ososinska. Lumen Publishing UK, 2020)
The article considers the problem of using information technology in teaching primary school students in Japan. It was studied the experience of Japan, where age is not an obstacle to the study new technologies in educational institutions. The Japanese are convinced that the basics of robotics should be learned by children at an early age. The study of IT as a discipline is aimed at instilling an interest in mathematics, science and technology. Children make the first attempts to create robots in elementary school. The need for the implementation of the studied areas and ways of teaching IT in Japan in the primary school of Ukraine is determined, the recommendations of the training and continuous support of teachers are formulated.
Keywords: reforming; personal computer; robotic technologies; electronic educational resources